2006
DOI: 10.1007/s11242-006-9019-x
|View full text |Cite
|
Sign up to set email alerts
|

Modern Methods of Drying Nanomaterials

Abstract: This paper presents the types of nanomaterials whose technology requires drying during processing. The methods of drying of three groups of nanomaterials are discussed: nanoparticles, nanolayers (nanofilms), and nanoporous materials. Principally the method of spray drying using ultrasonic nebulizers and electrospraying is presented for the first group. The Langmuir-Blogget technique is presented for the second group. The method of supercritical drying and the solvent replacement technique is described for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In order to avoid agglomeration, all ions and water have to be removed prior to drying 38) . Supercritical dr ying is another method reported to produce nanoparticles 38) .…”
Section: Dr Ying To Produce Nano-particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid agglomeration, all ions and water have to be removed prior to drying 38) . Supercritical dr ying is another method reported to produce nanoparticles 38) .…”
Section: Dr Ying To Produce Nano-particlesmentioning
confidence: 99%
“…Supercritical dr ying is another method reported to produce nanoparticles 38) . Supercritical dr ying is a process to remove liquid in a precisely controlled way.…”
Section: Dr Ying To Produce Nano-particlesmentioning
confidence: 99%
“…This means that the spray chamber required for drying can be much smaller. While these devices would appear to offer much promise for spray-drying applications [3,42,59,60,62,63,79], a review of the literature was unable to locate an article describing this approach to dairy fluids.…”
Section: Spray Drying Using Ultrasonic Atomizationmentioning
confidence: 99%
“…Spray drying (SD) is a well-established technique that has been used in many areas, including food, pharmaceutical, ceramic, polymer, and chemical industries [ 9 ]. The critical cost analysis of the spray-drying process has shown that it has advantages in labor and maintenance costs, which encouraged the acceptance of spray-drying as a standard industrial dehydration method [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%